2010
DOI: 10.1074/jbc.m110.137661
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones Up-regulate Insulin-like Growth Factor-1 Receptor via a Peroxisome Proliferator-activated Receptor γ-Independent Pathway

Abstract: There is increasing evidence that thiazolidinediones (TZDs), antidiabetic compounds that are synthetic ligands for the peroxisome proliferator-activated receptor ␥ (PPAR␥), have cardiovascular effects through as yet poorly defined mechanisms. We tested the effect of two TZD class drugs, rosiglitazone and pioglitazone, on human aortic smooth muscle cell (SMC) expression of insulin-like growth factor-1 receptor (IGF-1R). Both TZDs dose dependently up-regulated IGF-1R protein levels (rosiglitazone, 10 mol/liter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Receptor-independent actions of rosiglitazone and pioglitazone have been reported in previous literature 18, 31 and this study has identified numerous off-target interacting proteins involved in mitochondrial function, lipid/fatty acid metabolism, and glycolysis/gluconeogenesis regulation (Tables 1–4 and Supplemental Table 1). Previous literature has indicated that PPARγ antagonists and transcriptional/translational inhibitors do not abolish TZD effects 18, 32 , suggesting there are additional effects contributing to increasing insulin sensitivity.…”
Section: Discussionsupporting
confidence: 61%
“…Receptor-independent actions of rosiglitazone and pioglitazone have been reported in previous literature 18, 31 and this study has identified numerous off-target interacting proteins involved in mitochondrial function, lipid/fatty acid metabolism, and glycolysis/gluconeogenesis regulation (Tables 1–4 and Supplemental Table 1). Previous literature has indicated that PPARγ antagonists and transcriptional/translational inhibitors do not abolish TZD effects 18, 32 , suggesting there are additional effects contributing to increasing insulin sensitivity.…”
Section: Discussionsupporting
confidence: 61%
“…There is evidence showing that using insulin and insulin analogs to treat diabetes increases cancer rates as they may also activate IGF1R signaling (Gunter et al 2009, Hemkens et al 2009, Wilson 2011). The problem is compounded by a nationwide cohort study showing that most glucose-lowering antidiabetic medications, including thiazolidinediones and sulfonylureas, increase cancer risk (Higashi et al 2010, Andersson et al 2012. Therefore, efforts are needed to find new glucose-lowering agents with low carcinogenicity and other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cDNA microarray analysis of NIH-3T3 cells indicated that more than half of the genes upregulated by IGF1R activation are associated with mitogenesis and differentiation, whereas none of the genes specifically upregulated by IR activation are associated with these processes, suggesting that IGF1R activation is more mitogenic than IR activation (Dupont et al 2001b). Indeed, IGF1R activation has been found to be intimately associated with cancer development (Higashi et al 2010, Lewis et al 2010, Wu et al 2011, Huang et al 2012, Ma et al 2012. There is evidence showing that using insulin and insulin analogs to treat diabetes increases cancer rates as they may also activate IGF1R signaling (Gunter et al 2009, Hemkens et al 2009, Wilson 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations